Impact of Processing Conditions on Inter‐tablet Coating Thickness Variations Measured by Terahertz In‐Line Sensing. Issue 8 (2nd June 2015) - Lin, Hungyen; May, Robert K.; Evans, Michael J.; Zhong, Shuncong; Gladden, Lynn F.; Shen, Yaochun; Zeitler, J. Axel
<x xml:space="preserve">Abstract</x> A novel in‐line technique utilising pulsed terahertz radiation for direct measurement of the film coating thickness of individual tablets during the coating process was previously developed and demonstrated on a production‐scale coater. Here, we use this technique to monitor the evolution of tablet film coating thickness and its inter‐tablet variability during the coating process under a number of different process conditions that have been purposefully induced in the production‐scale coating process. The changes that were introduced to the coating process include removing the baffles from the coater, adding uncoated tablets to the running process, halting the drum, blockage of spray guns and changes to the spray rate. The terahertz sensor was able to pick up the resulting changes in average coating thickness in the coating drum and we report the impact of these process changes on the resulting coating quality. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2513–2522, 2015